Nutritional Evaluation Of Untreated And Ureatreated Rice Straw For Improved Utilization By Goats - Andrew, Alek Tuen (1998)

(untitled)
Rice straw is seldom used as goat feed despite reports of higher intake and digestibility of poor quality roughage by this species . Studies were conducted to evaluate local rice straw , define its limitation and investigate means to improve its utilization by goats. Compositional and degradability studies showed that untreated rice straw is deficient in N and several minerals and is poorly degraded . Calcium hydroxide and sodium hydroxide treatment increased degradability but the treated material was less acceptable to goats compared to rice straw treated with urea or ammonium hydroxide which has relatively lower degradability. Treatment with nitric acid removed all the hemicellulose and was totally unacceptable to goats. The ad libitum intake and in vivo digestibility of urea-treated straw was higher than that of urea supplemented straw and untreated straw .